2011
DOI: 10.1002/da.20853
|View full text |Cite
|
Sign up to set email alerts
|

Obsessions in normality and psychopathology

Abstract: Obsessions are common phenomena in the general population and are associated with decreased functioning in several areas of health and well-being. Furthermore, they occur frequently in the presence of various psychiatric disorders. Obsessions should be perceived, similar to delusions, as a distinct dimension across psychiatric disorders rather than a mere symptom of OCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…Regarding clinical severity, our results are consistent with previous studies assessing juvenile samples that demonstrated the presence of OCS in children is associated with increased levels of psychiatric symptom comorbidity and clinical impairment (Apter et al, 1996;Blom et al, 2011;Canals et al, 2012;Vivan et al, 2014;Voltas et al, 2014). Therefore, we agree with authors who suggest that threshold obsessive compulsive phenomena should be more actively and systematically investigated by primary care and mental health professionals ).…”
Section: Discussionsupporting
confidence: 95%
“…Regarding clinical severity, our results are consistent with previous studies assessing juvenile samples that demonstrated the presence of OCS in children is associated with increased levels of psychiatric symptom comorbidity and clinical impairment (Apter et al, 1996;Blom et al, 2011;Canals et al, 2012;Vivan et al, 2014;Voltas et al, 2014). Therefore, we agree with authors who suggest that threshold obsessive compulsive phenomena should be more actively and systematically investigated by primary care and mental health professionals ).…”
Section: Discussionsupporting
confidence: 95%
“…This is consistent with the literature [11,46]. However, although a higher number of individuals in the OCD and OCS groups had previously sought mental health services in comparison to controls, only 11.7 % of subjects from the OCD group had sought (or were referred to) mental health services [8,13].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, 67 % of OCD patients who sought treatment had comorbid major depression [38]. Likewise, Blom et al [39] reported that obsessions were associated with impairment in functioning and poorer quality of life in various domains, even after controlling for the effect of other mental disorders. In OCD, higher severity of obsessive thoughts and comorbid depression were also associated with poorer quality of life [48], which can lead to treatment seeking.…”
Section: Factors Associated With Overall and Dimensional Ocs Severitymentioning
confidence: 98%
“…Given that OCS are not exclusive to OCD, occurring even in people without any psychiatric disorder, recent community surveys [20,[38][39][40] have adopted a dimensional approach to evaluate the occurrence of OCS, including subclinical manifestations, rather than a categorical view (i.e., presence or absence of OCD diagnosis).…”
Section: Factors Associated With Overall and Dimensional Ocs Severitymentioning
confidence: 99%